2020
DOI: 10.21203/rs.3.rs-50275/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patients with COVID-19 Interstitial Pneumonia Exhibit Pancreatic Hyperenzymemia and Not Acute Pancreatitis

Abstract: Background and aims: Gastrointestinal manifestations of COVID-19 have been well established, but pancreatic involvement is under debate. The aim of the study is to evaluate the presence of acute pancreatitis in COVID-19 patients and to assess the frequency of pancreatic hyperenzymemia. Methods: From April 1st 2020 to April 30th 2020, 110 consecutive patients (69 males, 41 females; mean age 63.0 years, range 24-93 years) met these criteria and were enrolled in the study.. The clinical data and serum activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…The initial search yielded 52 articles. After excluding duplicates and review articles, 7 studies 3,6-10 (6 retrospective observational studies and 1 prospective observational study 11 ) were included in the pooled analysis. A flow chart depicting the study screening and selection process is presented in Supplementary Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The initial search yielded 52 articles. After excluding duplicates and review articles, 7 studies 3,6-10 (6 retrospective observational studies and 1 prospective observational study 11 ) were included in the pooled analysis. A flow chart depicting the study screening and selection process is presented in Supplementary Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In their retrospective analysis, Barlass et al found markedly elevated lipase levels in 14 of 83 (17%) patients who tested positive for COVID-19 and were admitted to the hospital [12]. As pointed by Pezzili et al [13], patients with COVID-19 infection may exhibit elevation of serum levels of pancreatic enzymes but they may not satisfy the diagnostic criteria for acute pancreatitis. In their cohort of 110 COVID-19 positive patients, 24.5% of them had increased amylase levels, 16.4% had increased lipase levels, but only a single patient (0.9%) had levels above three-fold the upper limit.…”
Section: Discussionmentioning
confidence: 96%
“…In their cohort of 110 COVID-19 positive patients, 24.5% of them had increased amylase levels, 16.4% had increased lipase levels, but only a single patient (0.9%) had levels above three-fold the upper limit. None of these patients developed clinical or morphological signs of acute pancreatitis [13]. The clinical significance of increased lipase levels in patients with COVID-19 has been questioned [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with COVID-19 infection may exhibit elevation of serum levels of pancreatic enzymes, but they may not develop clinical symptoms or otherwise satisfy the diagnostic criteria for acute pancreatitis [ 19 ]. This is also the reason why cases of COVID-19-induced pancreatitis are scattered [ 10 ].…”
Section: Discussionmentioning
confidence: 99%